Pengaruh Financial Leverage terhadap ROE dan EPS pada Perusahaan Perbankan BUMN yang terdaftar di BEI - Nisa Hafsyari Fauziah; Fatmi Hadiani; Tjetjep Djuwarsa (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
The aim of this final project is to find the affect of Financial Leverage towards Return on Equity and Earning Per Share at BUMN Banking Companies Listed on the IDX in period 2013-2020. This study used secondary data which was obtained indirectly from the company's financial report on the Indonesia Stock Exchange. This study used quantitative approach. The methods of analysis in this study used Descriptive Analysis, Classical Assumption Test, Coefficient of Determination, Linear Regression, and t-test using the IBM SPSS 25 application for windows. The results of this study indicate that Financial Leverage has no significant effect on ROE because the significance value of 0.569 is greater than 0.05 and at t-count < t table is 0.576 < 2.042 while Financial Leverage has a significant effect on EPS because the significance value of 0.037 is smaller than 0.05 and at t-count < t table that is -2.186 < -2.042.